Neuronal coding and spiking randomness - Kostal, Lubomir; Lansky, Petr; Rospars, Jean-Pierre (The European journal of neuroscience, 2007)
Fast information transfer in neuronal systems rests on series of action potentials, the spike trains, conducted along axons. Methods that compare spike trains are crucial for characterizing different neuronal coding schemes. In this paper we review recent results on the notion of spiking randomness, and discuss its properties with respect to the rate and temporal coding schemes. This method is compared with other widely used characteristics of spiking activity, namely the variability of interspike intervals, and it is shown that randomness and variability provide two distinct views. We demonstrate that estimation of spiking randomness from simulated and experimental data is capable of capturing characteristics that would otherwise be difficult to obtain with conventional methods.
Keywords: modely neurologické; Synaptic Transmission; Computer Simulation; počítačová simulace; Animals; Models, Neurological; elektrofyziologie; akční potenciály; Action Potentials; neurony; zvířata; nervový přenos; Neurons; Electrophysiology